Degradação Fotocatalítica de Corante Alimentício Azorrubina e Monitoramento de Redução de Toxicidade - de Souza, Danilo Rodrigues; de Miranda, Jacques Antonio; Oliveira, Karla Renata; Mapeli, Ana Maria; Santos, David de Jesus (Orbital: The Electronic Journal of Chemistry, 2016)
In present work, simples of the food dyes organic synthetic (C2OH12N2Na2O7S2) was submitted to photodegradation with a support of the Fenton and photo-Fenton reactions and measure toxicity with a support of essays germination of the lettuce seeds (Lactuca sativa). The results showed that, using Fenton and photo-Fenton reactions and simples dyes with a concentration of the 2500 ppm, were achieved 100% discoloration in only 30 minutes. The photocatalytic of the uv-vis light, uv-vis and H2O2, Fenton and photo-Fenton reactions, constant values presented apparent discolored of the, kap = 0.02161 min-1, kap = 0.04939 min-1, e kap = 0.1244 min-1, respectively. The reduction toxicity assays presented a significant reduction of toxicity after analyzing the samples collected in 120 minutes of the photolysis. The toxicity reduction achieved, compared to the control sample, was 17.43% for the growth of the radicle and 32.35% for the growth of the hypocotyl. DOI: http://dx.doi.org/10.17807/orbital.v1i1.717